2019
DOI: 10.1111/bph.14718
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ signalling plays a role in celastrol‐mediated suppression of synovial fibroblasts of rheumatoid arthritis patients and experimental arthritis in rats

Abstract: Background and Purpose Celastrol exhibits anti‐arthritic effects in rheumatoid arthritis (RA), but the role of celastrol‐mediated Ca 2+ mobilization in treatment of RA remains undefined. Here, we describe a regulatory role for celastrol‐induced Ca 2+ signalling in synovial fibroblasts of RA patients and adjuvant‐induced arthritis (AIA) in rats. Experimental Approach We used computational docking, Ca 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 68 publications
1
36
0
Order By: Relevance
“…Many studies showed the Tripterygium ingredients have the properties to promote FLS apoptosis and cell cycle arrest and inhibit FLS autophagy ( Xu, 2013 ; Xu et al., 2013 ; Lei et al., 2015 ; Su et al., 2017 ; Wong et al., 2019 ). It may be relevant to the increased expression of Bax/Bcl-2, Caspase-3, Caspase-9, and regulating by Ca2+/calmodulin-dependent protein kinases beta (CaMKK)-AMPK-mTOR signaling pathway.…”
Section: The Role Of Tripterygium Ingredients On Fls and The Moleculementioning
confidence: 99%
“…Many studies showed the Tripterygium ingredients have the properties to promote FLS apoptosis and cell cycle arrest and inhibit FLS autophagy ( Xu, 2013 ; Xu et al., 2013 ; Lei et al., 2015 ; Su et al., 2017 ; Wong et al., 2019 ). It may be relevant to the increased expression of Bax/Bcl-2, Caspase-3, Caspase-9, and regulating by Ca2+/calmodulin-dependent protein kinases beta (CaMKK)-AMPK-mTOR signaling pathway.…”
Section: The Role Of Tripterygium Ingredients On Fls and The Moleculementioning
confidence: 99%
“…Medicine have become important choices for the treatment of several chronic diseases, including liver fibrosis. 5,7 Celastrol is a pentacyclic triterpenoid compound 8,9 (the chemical structure of celastrol is shown in Figure 1), which is isolated from a common clinical used Traditional Chinese Medicine named Tripterygium wilfordii Hook F.…”
Section: The Active Ingredients Extracted From Traditional Chinesementioning
confidence: 99%
“…The active ingredients extracted from Traditional Chinese Medicine have become important choices for the treatment of several chronic diseases, including liver fibrosis . Celastrol is a pentacyclic triterpenoid compound (the chemical structure of celastrol is shown in Figure ), which is isolated from a common clinical used Traditional Chinese Medicine named Tripterygium wilfordii Hook F. Celastrol possesses multiple pharmacological effects and showed potent anti‐inflammatory effect against many disease models, and however, few reports can be seen regarding the anti‐inflammatory potential of celastrol in liver fibrosis. SIR2 is a family of histone deacetylases and is widely distributed in cells with multiple functions .…”
Section: Introductionmentioning
confidence: 99%
“…Modern research shows that triptolide has antitumor, anti‐cystogenesis, anti‐inflammatory and immunosuppressive activities, with applications in cancer treatment (Titov et al , Zhou et al , , Liu et al ). Celastrol, a red triterpenoid, shows effects against obesity (Fang et al ) and rheumatoid arthritis (Wong et al ).…”
Section: Introductionmentioning
confidence: 99%